Stimulation of Airway and Intestinal Mucosal Secretion by Natural Coumarin CFTR Activators - Yang, Hong; Xu, Lina; Sui, Yujie; Liu, Xin; He, Chengyan; Fang, Rouyu; Liu, Jia; Hao, Feng; Ma, Tong-Hui (Frontiers in Pharmacology, 2011)
Mutations of cystic fibrosis transmembrane conductance regulator (CFTR) cause lethal hereditary disease cystic fibrosis (CF) that involves extensive destruction and dysfunction of serous epithelium. Possible pharmacological therapy includes correction of defective intracellular processing and abnormal channel gating. In a previous study, we identified five natural coumarin potentiators of Δ508-CFTR including osthole, imperatorin, isopsoralen, praeruptorin A and scoparone. The present study was designed to determine the activity of these coumarine compounds on CFTR activity in animal tissues as a primary evaluation of their therapeutic potential. In the present study, we analyzed the affinity of these coumarin potentiators in activating wild-type CFTR and found that they are all potent activators. Osthole showed the highest affinity with Kd values <50 nmol/L as determined by Ussing chamber short-circuit current assay. Stimulation of rat colonic mucosal secretion by osthole was tested by the Ussing chamber short-circuit current assay. Osthole reached maximal activation of colonic Cl- secretion at 5 mol/L. Stimulation of mouse tracheal mucosal secretion was analyzed by optical measurement of single gland secretion. Fluid secretion rate of tracheal single submucosal gland stimulated by osthole at 10mol/L was 3-fold more rapid than that in negative control. In both cases the stimulated secretions were fully abolished by CFTRinh-172. In conclusion, the effective stimulation of Cl– and fluid secretion in colonic and tracheal mucosa by osthole suggested the therapeutic potential of natural coumarine compounds for the treatment of cystic fibrosis and other CFTR-related diseases.